Politics in the Russian Regions
XII, 219 p. 7 illus.
Keywords: This volume analyzes the changing power relations in the Russian regions and in their relationship with the centre. It considers Russian federalism and the changes that Putin has introduced, and the distribution of power at the regional level. The result is a rich survey of the state of federal relations in Russia.